2016
DOI: 10.1007/s11032-015-0430-2
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Crops Browser: a bridge between model and orphan crops

Abstract: Many important crops have received little attention by the scientific community, either because they are not considered economically important or due to their large and complex genomes. De novo transcriptome assembly, using next-generation sequencing data, is an attractive option for the study of these orphan crops. In spite of the large amount of sequencing data that can be generated, there is currently a lack of tools which can effectively help molecular breeders and biologists to mine this type of informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…Most of the publicly available software tools offer limited options, forcing researchers to use a combination of open software packages, requiring in general different formats and operational systems (Deng, 2011). Based on the identification of the putative TCP transcripts for both bulbous species, we confirmed that the Transcriptome Browser (Kamei et al, 2016) represents a reliable and user-friendly web based interface, able to identify gene families and build phylogenetic relationships with other species.…”
Section: Functionality Of the Transcriptome Browser In Mining The Extsupporting
confidence: 52%
See 2 more Smart Citations
“…Most of the publicly available software tools offer limited options, forcing researchers to use a combination of open software packages, requiring in general different formats and operational systems (Deng, 2011). Based on the identification of the putative TCP transcripts for both bulbous species, we confirmed that the Transcriptome Browser (Kamei et al, 2016) represents a reliable and user-friendly web based interface, able to identify gene families and build phylogenetic relationships with other species.…”
Section: Functionality Of the Transcriptome Browser In Mining The Extsupporting
confidence: 52%
“…To support in mining data using open sources, we decided to deposit our generated transcriptomes in a web-browser (http://www.bioinformatics.nl/bulbs/db/species/index) based on recently developed open software (Kamei et al, 2016). This web-based interface offers basic bioinformatics search tools, identification of candidate transcripts based on phylogenetic relationships between orthologous sequence data and design of specific and degenerate primers for expression studies of transcripts of interest (Fig.…”
Section: Identification Of the Tcp Gene Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Kamei et al (2016) developed a tool that enables molecular breeders even without extensive bioinformatics knowledge to efficiently study de novo transcriptome data from any crop (Orphan Crop Browser; http://www.bioinformatics.nl) with a large and complex genome. They used that tool to identify the putative orthologues of 17 known lignin biosynthetic genes from maize and sugarcane in the orphan crop Miscanthus sinensis Andersson.…”
Section: Transcriptome Researchmentioning
confidence: 99%
“…Subsequently, a web-based interface (Kamei et al 2016), which we call Transcriptome Browser, was implemented for data presentation and mining.…”
Section: Introductionmentioning
confidence: 99%